(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This scientific article analyzes the impact of the processes of humanization and democratization of the education system in the Republic of Uzbekistan on the creative activity of young people. The study examines the role of individual-oriented models of education based on modern pedagogical approaches, the introduction of democratic principles and their importance in developing the creative potential of young people. The article presents analytical materials on educational reforms being implemented in Uzbekistan, innovative methods combined with national values, as well as the effectiveness of spiritual and educational work.